S.D. Terr. Pen. Code (1877), &sect - (:unkn) unknown (My University, 1877)
Prohibited the carrying, "whether concealed or not," of any slungshot, and prohibited the concealed carrying of any firearms or sharp or dangerous weapons.
457 as codified in S.D. Rev. Code, Penal Code (1903), &sect
&sect
Keywords: CARRY; CARRY - CONCEALED